THE ROLE OF INNOVATIVE BANKING SERVICES AND THEIR IMPACT ON BANKING INCOME - Berdiboev , Oltinboy (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
The introduction of modern services in commercial banks was analyzed based on the experience of developed countries and scientific research, and it was determined that innovative banking services are an important factor in increasing the net profit of banks. The widespread introduction of digital services contributes to the efficiency, competitiveness, and increase in the number of clients of banks.